GENERALIZED ESTABLISH JENSEN TYPE ADDITIVE λ1; λ2-FUNCTIONAL INEQUALITIES WITH 3k-VARIABLES IN α1; α2-HOMOGENEOUS F-SPACES - AN, LY VAN (International Journal For Research In Mathematics And Statistics, 2023)
In this paper, we study to solve two additive λ1; λ2-functional inequalities with 3k-variables in α1; α2-homogeneous F spaces. Then we will show that the solutions of the first and second inequalities are additive mappings.That is the main result in this paper.